CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN KINERJA KEUANGAN PADA PT. PUPUK KALTIM - Camelia Verahastuti, Sayanti, Titin Ruliana (EKONOMIA, 2015)
The purpose the research is to examine the effect of corporate social responsibility (CSR Disclosure) to the financial performance at Pupuk Kaltim limited liability company. Basic Theory used is financial accounting, corporate social responsibility and financial performance. In this researchs the companyâ€™sÂ financial performance is measured by using Return On Asset (ROA), Return On Equity (ROE), Return On Sales (ROS) and Current Ratio. Independent variables used in this research is the Corporate Social Responsibility with 79 disclosure according GRI, while the dependent variable is financial performance.Research sample was Pupuk Kaltim limited liability company, year research periode 2012-2014. Data collected by the method of documentary and literature.The research data is analyzed by using simple linear regression with SPSS V.20The result showed that the corporate social responsibility (CSR) has no significant effect on the financial performance. This is shown ROA = Sig 0.488 > 0.05, ROE = Sig 0.821 > 0.05, ROS = Sig 0.821 > 0.05 and Current Ratio = Sig 0.184 > 0.05